PERLINDUNGAN HUKUM MASYARAKAT TERHADAP KEWAJIBAN VAKSINASI COVID 19 DALAM RANGKA PENANGGULANGAN PANDEMI CORONA VIRUS DISEASE 19 - Ayu Wulandari Wirawan, Wahyudi, (Res Nullius Law Journal, 2022)
This study aims to determine the legal protection of the community against the obligation to vaccinate covid 19 based on government decisions with the aim of tackling the spread of the corona virus pandemic 19. The method used in this study is a normative juridical approach, the data obtained were analyzed qualitatively juridically by taking into account the hierarchy of provisions. current regulation. The results of this study indicate that people have rights to themselves and can determine what is best for their bodies, including vaccines. The covid 19 pandemic that hit Indonesia affected various sectors, from the health sector to the economy. The government as a representative of the state in protecting all levels of society takes the necessary steps to tackle the spread of covid 19 by making decisions to limit community activities and also decisions to provide vaccines to the community and require vaccines for people who have been designated as the target recipients of the covid 19 vaccine. Article 5 paragraph (3) of Law No. 36 of 2009 concerning Health states that the public as vaccine recipients have autonomous rights over themselves. However, during a pandemic, the government may oblige to vaccinate people who have been designated as the target recipients of the covid 19 vaccine based on Article 13A paragraph (2) of Presidential Regulation of the Republic of Indonesia Number 14 of 2021 concerning Amendments to Presidential Regulation Number 99 of 2020 concerning Vaccine Procurement and Implementation of Vaccination in the Context of Combating the Covid 19 Pandemic.